Predictive factors for long-term patency in duodenal stenting for malignant gastric outlet obstruction - Razzaz, David; Linder, Stefan; Waldthaler, Alexander; Holmberg, Marcus; Ghorbani, Poya (Endoscopy International Open, 2025)
Malignant gastric outlet obstruction (GOO) occurs often late during disseminated disease, requiring palliation. Placement of duodenal self-expandable metal stents (SEMS) is a common method for relieving malignant GOO but recurrent obstruction is common, warranting reintervention. The aim of the present study was to identify predictive factors for stent patency at 3 months and survival. Also, stent patency rate and adverse events after duodenal stenting were analyzed.This was a retrospective observational single-center study including all patients with malignant GOO receiving duodenal SEMS for palliation (2008–2021). Logistic regression for stent patency (3 months) and Cox regression for survival were undertaken.Overall, 198 patients were included. The most common malignancies were pancreatic adenocarcinoma (40%), gastric adenocarcinoma (18%), and cholangiocarcinoma (13%). Uncovered SEMS were used in 88% of patients and the reintervention rate was 44%. The stent patency rate was 63% in 188 patients with clinical success. Predictors of stent patency at 3 months were jaundice, semi- or fully-covered stents, and chemotherapy prior to stenting. Median survival was 81 days (interquartile range 40–241) after stenting. In Cox regression, predictors for overall survival at 6 months were absence of jaundice and stent patency at 3 months. Stent dysfunction was the most common cause of reintervention and was managed by repeated stent (76%) or dilation (11%).Treatment of malignant GOO with duodenal SEMS is effective but the reintervention rate is high. Predictors of stent patency were jaundice, semi- or fully-covered SEMS, and chemotherapy. Survival was impaired by jaundice and stent dysfunction.
Keywords: Endoscopy Upper GI Tract; Malignant strictures; Dilation, injection, stenting; Pancreatobiliary (ERCP/PTCD); Strictures